Temperature-dependent absorption cross section measurements for propene, 1-butene, cis-/trans-2-butene, isobutene and 1, 3-butadiene in the spectral region 8.4–11.7 µm. (November 2020) - Ding, Yiming; Su, Wey-Wey; Johnson, Sarah E.; Strand, Christopher L.; Hanson, Ronald K.
Highlights: Employed a broad-scan, rapid-tuning EC-QCL for the collection of high-temperature absorption spectra in a shock tube. Validated the experimental procedure with room-temperature, nitrogen-diluted, static spectra measurements at one atmosphere. Reported the absorption spectra for propene, 1-butene, cis-/trans-2-butene, isobutene and 1, 3-butadiene between 8.4–11.7 µm and 600–1000 K Found good agreement between the measured spectra and absorption predictions from cross section correlations in the literature. Efficiently expanded upon existing spectroscopic knowledge of mid-infrared absorption at combustion-related conditions. Abstract: We present a comprehensive study on the temperature-dependent mid-infrared absorption spectra between 8.4 µm and 11.7 µm for a complete list of C3 -C4 alkenes, namely propene, 1-butene, cis-/trans-2-butene and isobutene, as well as 1, 3-butadiene, from room temperature to roughly 1000 K. The methodology deploys a rapid-tuning, broad-scan external-cavity quantum-cascade laser (EC-QCL) in a shock tube and can provide quantitative absorption information at a rate in excess of 30 cm − 1 /ms at spectral intervals between 0.35–0.6 cm − 1 . The experimental procedure was validated with room-temperature, nitrogen-diluted, static spectra measurements for propene, 1-butene, isobutene, and 1, 3-butadiene, showing good agreement with existing spectroscopic databases. Spectral measurements were extended to higher temperatures with shock-heated test gas mixtures diluted by argon, at experimental conditions between 600–1000 K and 1.5–2.5 atm. The resulting spectra show strong temperature dependence and represent the first experimental collection of broadband high-temperature absorption spectra for these species. The measured high-temperature spectra are in reasonable agreement with predictions from fixed-wavelength absorption cross section correlations in the literature. The data presented are archived in the Stanford ShockGas-IR database and provide useful expansions of the existing knowledge on molecular absorption in the mid-infrared at elevated temperatures.